Elevated serum copper and ceruloplasmin levels in Alzheimer's disease - Park, Jun-Hyun; Lee, Dong-Woo; Park, Kyung Soo (WILEY, 2014)
IntroductionCopper takes part in a variety of biological reduction-oxidation (redox) processes, and is an important cofactor of many redox enzymes. Ceruloplasmin, the copper-transporting protein, also possesses an important redox capacity. MethodsWe assessed serum copper, ceruloplasmin and free-copper levels in 89 patients with Alzheimer's disease (AD) (mean age, 77.83 years; 41 men, 48 women) and in 118 healthy individuals (mean age, 69.93 years; 50 men, 68 women). High (75th percentile), medium, and low (25th percentile) copper, ceruloplasmin and free-copper groups were classified according to their serum level. ResultsSerum copper (P=0.026) and ceruloplasmin (P=0.001) levels were significantly higher in the AD group than in the control group. There was no significant difference in serum free-copper levels between AD and healthy elderly groups (P=0.975). After adjusting for age differences, serum copper (P=0.049) was still significantly higher in the AD group. Furthermore, serum copper levels correlated with scores on the Boston naming test (r=-0.151, P=0.037), indicating a close relationship between copper levels and cognitive abilities. DiscussionThe significant association between the copper concentration in peripheral serum and AD with elevated copper levels found in patients with AD is likely linked to the evolution of AD. Serum copper levels were significantly negatively correlated with scores on cognitive test subscores. AD patients may have significantly more defective ceruloplasmin, that is, apo-ceruloplasmin lacking its copper, than in healthy controls.
Keywords: CEREBROSPINAL-FLUID; LOCUS-COERULEUS; SUPEROXIDE-DISMUTASE; METAL-IONS; PLASMA; ZINC; MALONDIALDEHYDE; ATTENTION; TOXICITY; DEMENTIA